Do Gray Whales Count Calories? Comparing Energetic Values of Gray Whale Prey Across Two Different Feeding Grounds in the Eastern North Pacific - Hildebrand, Lisa; Bernard, Kim S.; Torres, Leigh G. (Frontiers in Marine Science, 2021)
Predators must consume enough prey to support costly events, such as reproduction. Meeting high energetic requirements is particularly challenging for migrating baleen whales as their feeding seasons are typically restricted to a limited temporal window and marine prey are notoriously patchy. We assessed the energetic value of the six most common nearshore zooplankton species collected within the Oregon, United States range of the Pacific Coast Feeding Group (PCFG) gray whale (Eschrichtius robustus) feeding grounds, and compared these results to the energetic value of the predominant amphipod species fed on by Eastern North Pacific (ENP) gray whales in the Arctic. Energetic values of Oregon zooplankton differed significantly between species (Kruskal–Wallis χ2 = 123.38, df = 5, p < 0.0001), with Dungeness crab (Cancer magister) megalopae displaying the highest mean caloric content of all tested species (4.21 ± 1.27 kJ g– 1). This value, as well as the mean energetic value of the mysid Neomysis rayii (2.42 ± 1.06 kJ g– 1), are higher than the mean caloric content of Ampelisca macrocephala, the predominant Arctic amphipod. Extrapolations of these results to daily energetic requirements of gray whales indicate that lactating and pregnant gray whales feeding in the PCFG range would require between 0.7–1.03 and 0.22–0.33 metric tons of prey less per day if they fed on Dungeness crab megalopae or N. rayii, respectively, than a whale feeding on A. macrocephala in the Arctic. Yet, these results do not account for differences in availability of these prey species to foraging gray whales. We therefore suggest that other factors, such as prey density, energetic costs of feeding, or natal philopatry and foraging site fidelity play a role in the differences in population sizes between the PCFG and ENP gray whales. Climate change is implicated in causing reduced body condition and increased mortality of both PCFG and ENP gray whales due to decreased prey availability and abundance. Therefore, improved understanding of prey dynamics in response to environmental variability in both regions is critical.